Tunisia : 2006 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Tunisia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Tunisia showed excellent economic performance. Executive Directors commended the strong economic performance and resilience to adverse shocks, subdued inflation, strengthened reserves, and increasing capital inflows, which underscored the benefits of sustained sound macroeconomic policies and market-oriented reforms. They agreed that most of the key recommendations of the 2002 Financial Sector Assessment Program (FSAP) have been implemented. They welcomed the partial privatization of Tunisie Telecom to retire external debt and the completion of the Anti-Money Laundering and Combating Finance for Terrorism Report on the Observance of Standards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet